MENGELOLA KONFLIK ANTARA WARGA DESA DAN WARGA KAWASAN INDUSTRI (KASUS PADA KESENJANGAN SOSIAL DI KAWASAN INDUSTRI DI KABUPATEN BEKASI, JAWA BARAT) - ., Hamluddin (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2014)
The rapid growth of industry and economy in Bekasi make it as the biggest industrial area in Southeast Asia. However, this industrial and economic growth can only be felt by the citizens who live inside the seven industrial area. While the others , namely the natives, live in the outskirt of the industrial area. They are left behind and less-fortunate than those who live inside the industrial area.The gap between the industrial citizen and the native in Kabupaten Bekasi influences the interaction intensity among these citizens. From the native point of view, they feel reluctant to communicate with those who live in industrial area due to the differences in social and economic status. On the other hand, those who live in industrial area think that they don?t have any spare time to socialize or get in-volved with the natives.This research aims to: (1) find out how the citizens inside and outside the industrial area communicate with one another socially; (2) How does the rela-tionship of these two citizens influence the harmony and the conflict between them.